Lexikon der Bibelhermeneutik: Begriffe, Methoden, Theorien, Konzepte - Wischmeyer, Oda; Luther, Susanne (De Gruyter Studium, 2012)
Biographical note: Oda Wischmeyer, Friedrich-Alexander-Universität Erlangen-Nürnberg; Emil Angehrn, Universität Basel, Schweiz; Eve-Marie Becker,Universität Århus, Dänemark; Mechthild Habermann,Friedrich-Alexander-Universität Erlangen-Nürnberg; Ulrich H. J. Körtner,Universität Wien, Österreich; James Alfred Loader, Universität Wien, Österreich; Christine Lubkoll, Friedrich-Alexander-Universität Erlangen-Nürnberg; Karla Pollmann, University of St. Andrews, Großbritannien; Marco Schöller, Universität zu Köln; Günter Stemberger, Universität Wien, Österreich; Wolfgang Wischmeyer, Universität Wien, Österreich.